Does the choice between bank loans and bonds affect firm performance? Evidence from the Russian Federation. - Davydov, Denis (My University, 2009)
This study aims to examine the relationship between the choice of debt sources and firm performance. The financial data for the sample of 100 companies that are listed on the Russian stock exchanges was manually gathered and examined for the period from the 1st of January of 2004 until the 31st of December 2007. Cross-sectional analysis of the gathered data showed that debt structure affects firm value. Thus firms with public debt perform better than firms with private debt based on the market measure of performance – Tobin’s q. Additional analysis showed that firms with previous public history outperform those that initially make public offerings and those which rely on private debt, while another finding suggests that firms with initial public debt offerings experiencing higher return on equity. Finally, the estimation of the effect of switching from private bank loans to publicly placed debt reveled that after such substitution firms became much more leveraged and showed sustainable growth. However, based on the market measure of performance there appeared to be that these companies experienced a decline in their performance.
Keywords: Public debt; Private debt; Firm performance; Capital structure; fi=Finance and Accounting|; fi=Master's Degree Programme in Finance|